2020
DOI: 10.1016/j.jamcollsurg.2019.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Procedure Type, Case Duration, and Adjunctive Equipment on Surgeon Intraoperative Musculoskeletal Discomfort

Abstract: BACKGROUND: Surgeons are at high risk of developing musculoskeletal disorders. STUDY DESIGN: This study was designed to identify risk factors and assess intraoperative physical stressors using subjective and objective measures, including type of procedure and equipment used. Wearable sensors and pre-and postoperation surveys were analyzed. RESULTS: Data from 116 cases (34 male and 19 female surgeons) were collected across surgical specialties. Surgeons reported increased pain in the neck, upper, and lower back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 31 publications
(23 reference statements)
1
12
0
6
Order By: Relevance
“…It has been previously reported that, although loupes offer several advantages such as portability and cost-effectiveness, procedures performed with them are associated with extreme neck angles and increased muscle workload [ 13 , 44 ]. On the other hand, operating with the use of a microscope allows surgeons to maintain a neutral head position and offers a better view of the surgical field [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that, although loupes offer several advantages such as portability and cost-effectiveness, procedures performed with them are associated with extreme neck angles and increased muscle workload [ 13 , 44 ]. On the other hand, operating with the use of a microscope allows surgeons to maintain a neutral head position and offers a better view of the surgical field [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the results in this study, we speculate that a comprehensive 2-team approach would reduce stress on the surgeon. Objective data on surgeon stress need to be measured to clarify the influences of the approach on operator stress [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seratus enam belas ahli bedah melaporkan bahwa rasa sakit dan kelelahan fisik yang timbul disebabkan oleh lama durasi pembedahan. 4 Posisi yang sama dalam waktu yang lama dan bekerja dalam posisi yang canggung juga berkontribusi terhadap perkembangan gangguan muskuloskeletal. 5 Nyeri yang timbul di leher, punggung atas, dan punggung bawah selama dan setelah operasi pada ahli bedah dipengaruhi oleh postur fisik dan lama durasi saat melakukan operasi sehingga perlu diperhatikan kembali mengenai faktor ergonomis.…”
Section: Pendahuluanunclassified
“…5 Nyeri yang timbul di leher, punggung atas, dan punggung bawah selama dan setelah operasi pada ahli bedah dipengaruhi oleh postur fisik dan lama durasi saat melakukan operasi sehingga perlu diperhatikan kembali mengenai faktor ergonomis. 4 Tujuan scoping review ini mengetahui pengaruh lama dan posisi kerja terhadap keluhan muskuloskeletal pada petugas medis.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation